(Invited) Junctionless Device Cross-Section: A Key Aspect for Overcoming Boltzmann Tyranny. (24th April 2020) - Kranti, Abhinav; Gupta, Manish
Abstract : In this work, we report on the significance of device cross-section of a 3-dimensional Junctionless transistor (JLT) to facilitate a sharp rise in drain current with a low value (< 10 mV/decade) of subthreshold swing ( S S ). The analysis shows that apart from the usual device parameters such as gate length and drain voltage, the cross-section of a tri-gate JLT offers an additional degree of freedom to tune the extent of impact ionization in JLT. Results demonstrate that tri-gate JLT designed with lower aspect ratio (< 0.5) and wider film is most appropriate to overcome Boltzmann tyranny. The work highlights the usefulness of cross-sectional area for achieving sharp rise in drain current in JLT.